Medial Amygdala Lesions Selectively Block Aversive Pavlovian–Instrumental Transfer in Rats - McCue, Margaret G.; LeDoux, Joseph E.; Cain, Christopher K. (Frontiers in Behavioral Neuroscience, 2014)
Pavlovian conditioned stimuli (CSs) play an important role in the reinforcement and motivation of instrumental active avoidance (AA). Conditioned threats can also invigorate ongoing AA responding (aversive Pavlovian-instrumental transfer or PIT). The neural circuits mediating AA are poorly understood, although lesion studies suggest that lateral, basal and central amygdala nuclei, as well as infralimbic prefrontal cortex, make key, and sometimes opposing, contributions. We recently completed an extensive analysis of brain c-Fos expression in good vs. poor avoiders following an AA test (Martinez et al 2013, Learning and Memory). This analysis identified medial amygdala (MeA) as a potentially important region for Pavlovian motivation of instrumental actions. MeA is known to mediate defensive responding to innate threats as well as social behaviors, but its role in mediating aversive Pavlovian-instrumental interactions is unknown. We evaluated the effect of MeA lesions on Pavlovian conditioning, Sidman two-way AA conditioning (shuttling) and aversive PIT in rats. Mild footshocks served as the unconditioned stimulus in all conditioning phases. MeA lesions had no effect on AA but blocked the expression of aversive PIT and 22 kHz ultrasonic vocalizations in the AA context. Interestingly, MeA lesions failed to affect Pavlovian freezing to discrete threats but reduced freezing to contextual threats when assessed outside of the AA chamber. These findings differentiate MeA from lateral and central amygdala, as lesions of these nuclei disrupt Pavlovian freezing and aversive PIT, but have opposite effects on AA performance. Taken together, these results suggest that MeA plays a selective role in the motivation of instrumental avoidance by general or uncertain Pavlovian threats.